2015
DOI: 10.1109/ted.2015.2443859
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nongray Thermal Transport on the Temperature of AlGaN/GaN HFETs

Abstract: The hotspot temperature in AlGaN/GaN heterostructure FETs has been of great interest due to its effect on the reliability of these devices. Both the nanoscale heat transfer effects and complex energy transfer mechanism from electrons to lattice are factors affecting the hotspot temperature, which is not accounted for in continuum level thermal simulations. The effects of heat generation zone size and the energy transfer mechanism from electrons to the lattice on the hotspot temperature were analyzed using elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…According to fully coupled electrothermal simulation [158,175,178] shown in Fig. 12(a), the domain size of the peak heat generation zone can be less than 10 nm  50 nm, which is in agreement with theoretical predictions in literature [172,179].…”
Section: Nanoscopic Heat Flow Constriction In Wide Bandgapsupporting
confidence: 86%
See 3 more Smart Citations
“…According to fully coupled electrothermal simulation [158,175,178] shown in Fig. 12(a), the domain size of the peak heat generation zone can be less than 10 nm  50 nm, which is in agreement with theoretical predictions in literature [172,179].…”
Section: Nanoscopic Heat Flow Constriction In Wide Bandgapsupporting
confidence: 86%
“…Currently, industrial practices for device thermal analysis and accelerated direct current operational life tests [157,169] rely on simulation data based on the simple and widely accepted Fourier's law of heat conduction. However, a limited number of pioneering theoretical studies [170][171][172][173][174] have suggested that a nanoscale temperature spike or a so-called hot-spot forms in GaN HEMTs, which can be significantly hotter than predictions based on purely diffusive thermal transport models (i.e., the Fourier's law of heat conduction). This unanswered question has inhibited the use of GaN devices for high power RF applications where demonstrated long product lifetimes are required [158,175].…”
Section: Nanoscopic Heat Flow Constriction In Wide Bandgapmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the interface of GaN/SiC is a thick AlN nucleation layer with 20 nm thickness that involves intricate resistance mechanisms, including defects, dislocations, and interfacial disorders, these mechanisms seriously damage the thermal property, therefore heat spreading capacity of this interface of GaN/SiC was represented as a single effective interface thermal resistance in our model. Finally, to reduce the total computing time, only a quarter of device was simulated, because of their structural symmetry [3,[12][13][14][15][16][17][18][19][20][21].…”
Section: Device Details and Simulation Methodsmentioning
confidence: 99%